Investigating the effect of putrescine and salinity stress on some germination indices of Henna seeds (South Kerman's native) - Abolghasem Hamidi Moghaddam (علوم و فناوری بذر ایران)
Henna (Lawsonia inermis L.) is an ornamental and medicinal plant containing Lawson’s active substance, which is cultivated in some regions of the south and southeast of Iran. Salinity is one of the major abiotic environmental stress that affects almost all stages of plant development. Polyamines such as putrescine can play important roles in plant growth and stress responses. In order to investigate the effect of putrescine and NaCl salinity stress on some germination indices, a factorial experiment was conducted with two levels of putrescine (0 and 0.75 mM) and four salinity levels (0, 50, 100 and 150 mM) based on completely randomized design with four replications in germinator for 11 days. The results showed that at control salinity level, there was no significant difference between putrescine treatments on Henna seed germination indices except the seed vigor index. The interaction between putrescine and salinity stress showed that pre-treatment with putrescine alleviated the negative effects of 50 and 100 mM salinity stress on the germination rate. However, it increased the negative effects of 150 mM salinity stress on germination percentage, radicle length, plumule length, seedling fresh weight, seed vigor index and α-amylase activity in comparison to control. The results showed that germination of Henna seeds is sensitive to salinity stress and they are only able to tolerate low levels of salinity (50 mM). According to a significant correlation between α-amylase activity with germination percentage (r= 0/98), it can be concluded that probably the change in α-amylase activity decreased the germination percentage.